Spletni nabiralnik za oddajo elektronskih publikacij - Štular Sotošek, Karmen (Knjižnica, 2008)
The paper describes the new web service SVAROG - system for safe archiving of electronic publications - which has been created at the National and University Library in the second half of 2007. This service provides the deposit of digital material. It is intended for publishers and others who should supply the legal deposit copies of electronic publications, or to forward the statement on the conditions of use and access to electronic material. It also serves to communicate the information on new publications. Likewise, the service is designed for other content providers, including libraries and other institutions in the fieldsof culture, science and education, to supply the digitized material of the physical originals. In addition, the web system facilitates NUK to confirm the receipt by sending a notice to the submitter.
Keywords: spletne storitve; elektronske publikacije; obvezni izvod; digitalne knjižnice; založništvo; založniki; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana